Subretinal Injection of Recombinant Tissue Plasminogen Activator and Gas Tamponade to Displace Acute Submacular Haemorrhages Secondary to Age-Related Macular Degeneration - Iannetta D (Dove Medical Press, 2021)
Danilo Iannetta,1 Michele De Maria,1 Elena Bolletta,2 Valentina Mastrofilippo,1 Antonio Moramarco,1 Luigi Fontana1 1Ophthalmology Unit, Azienda USL-IRCCS di Reggio Emilia, Reggio Emilia, Italy; 2Ocular Immunology Unit, Azienda USL-IRCCS di Reggio Emilia, Reggio Emilia, ItalyCorrespondence: Danilo IannettaOphthalmology Unit, AUSL-IRCCS Reggio Emilia, Viale Risorgimento 80, Reggio Emilia, ItalyTel +39 0522296520Fax +39 0522295839Email iannettadanilo@gmail.comPurpose: To analyse the efficacy of subretinal injection of recombinant tissue plasminogen activator (rtPA) and gas tamponade for the displacement of submacular haemorrhage (SMH).Methods: This single-centre, retrospective, case series included 25 consecutive patients (25 eyes) who underwent pars plana vitrectomy (PPV) with subretinal rtPA injection and 20% sulphur hexafluoride (SF6) tamponade. The primary outcome was SMH displacement rate, defined as the absence of subretinal blood within (complete) or outside (partial) 1500 μm centred on the fovea one month after PPV. Secondary outcomes were final best-corrected visual acuity (BCVA), central macular thickness (CMT), recurrence probability, number of anti-vascular endothelial growth factor (VEGF) injections after PPV, and intra- and post-operative complications.Results: Successful displacement was obtained in all 25 eyes (100%), with complete and partial displacement obtained in 15 (60%) and 10 (40%), respectively. BCVA significantly improved from 1.81± 0.33 to 1.37± 0.52 LogMar at 12 months from surgery (p = 0.001). The bivariate correlation analysis revealed that earlier the surgery had better visual prognosis at the end of the follow-up (p = 0.007). CMT significantly decreased from 922 ± 273.69 μm at baseline to 403.53 ± 314.64 μm at 12 months follow-up (p < 0.001). SMH recurrence was observed in two (8%) patients with a mean survival time of 11.6 ± 0.339 months and a cumulative survival probability of 88% at the end of follow-up. After PPV, the mean number of anti-VEGF injections was 3.00 ± 0.957 with no correlation with final visual acuity (p = 0.365). No intraoperative complications were recorded. Only one patient developed open funnel retinal detachment 40 days after primary PPV.Conclusion: PPV with rtPA subretinal injection and SF6 tamponade is a safe and effective technique in displacing acute SMHs secondary to neovascular AMD. It is recommended to perform within 14 days from the onset of the symptoms to achieve BCVA improvement at 12 months and proper imaging to plan future anti-VEG treatment.Keywords: macular degeneration, submacular haemorrhage, recombinant tissue plasminogen activator, pars plana vitrectomy, subretinal injection